2019
DOI: 10.1007/s12034-019-1736-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparing photocatalytic paper with improved catalytic activity by in situ loading poly-dopamine on cellulose fibre

Abstract: Photocatalytic paper is a composite photocatalyst generally prepared by loading semiconductors, such as titanium dioxide (TiO 2) nanoparticles on paper, and attracts sustaining interests. In this paper, poly-dopamine (PDA) was loaded on cellulose fibre by in situ oxidative polymerization of dopamine. The PDA-loaded cellulose fibre (PLCF) was used to make TiO 2 photocatalytic paper together with pristine cellulose fibre (CF) and TiO 2 nanoparticles to improve the performance of the photocatalytic paper. The loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In case of blank paper, the cellulosic matrix appeared open, porous, and randomly dispersed (Figure 7a), whereas in the 1.0% TiO 2 -modified paper sheet, the porous structure was lost and the cellulosic fibers were uniformly coated and cross-linked to each other (Figure 7b). SEM investigation confirmed the AFM results: TiO 2 nanoparticles are dispersed on the surface of cellulosic matrix, although some aggregates occurred (evidenced by red arrows in Figure 7c), probably due to some retention effects of sodium-alginate on TiO 2 nanoparticles [40]. As expected, the EDAX analysis revealed that in the case of blank paper the most intense signals are due to C and O: the main constituents of the paper sheets (Figure 7d).…”
Section: Structural and Morphological Characterization Of Tio 2 −Modisupporting
confidence: 80%
See 1 more Smart Citation
“…In case of blank paper, the cellulosic matrix appeared open, porous, and randomly dispersed (Figure 7a), whereas in the 1.0% TiO 2 -modified paper sheet, the porous structure was lost and the cellulosic fibers were uniformly coated and cross-linked to each other (Figure 7b). SEM investigation confirmed the AFM results: TiO 2 nanoparticles are dispersed on the surface of cellulosic matrix, although some aggregates occurred (evidenced by red arrows in Figure 7c), probably due to some retention effects of sodium-alginate on TiO 2 nanoparticles [40]. As expected, the EDAX analysis revealed that in the case of blank paper the most intense signals are due to C and O: the main constituents of the paper sheets (Figure 7d).…”
Section: Structural and Morphological Characterization Of Tio 2 −Modisupporting
confidence: 80%
“…One possible reason for the observed decrement is found in the negative effects of dye accumulation on the pores of paper, which could be responsible for the coverage of catalyst surface: the intensity of light reaching the surface of catalyst nanoparticles was reduced, thus lowering the number of the photogenerated hole−electron pairs [54]. On the other hand, the degradation of paper after its continuous immersion in water could not be ruled out, which could cause the loss of some TiO 2 nanoparticles, and therefore a slight decrease in the photocatalytic efficiency [40,48].…”
Section: Photocatalityc Properties Of Tio 2 -Modified Papermentioning
confidence: 99%
“…As shown in Figure l, the ratio of O on the PDA–CCFN surfaces sharply increases, and N appears owing to the loading of PDA. Comparing the FTIR spectrum of the CCFN with that of the PDA–CCFN (Figure S2b, Supporting Information), one can find that new absorption bands attributed to the C–O stretching vibration of catechol and N–H shearing vibration appear at 1280 and 1509 cm –1 , respectively, further proving the loading of PDA on the CCFs Figure , parts i–k and m–p, shows the top-view and cross-section SEM images of the PDA–CCFN, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, taking advantage of the pore structure created by a reticular fiber network, it has been previously reported that paper was employed as an enhanced support material for gas phase catalytic reactions [55]. Photocatalytic paper is not considered a disposable product anymore, as it can be reutilized several times for the degradation of organic modeling dyes [58].…”
Section: Photocatalytic Papermentioning
confidence: 99%
“…The ratio of carbon/cellulose fibers also demonstrated to influence the MO photodegradation. Qin et al [58] described the production of photocatalytic papers containing a mixture of poly-dopamine-loaded cellulose fibers and pristine cellulose fibers and TiO 2 nanoparticles. The photocatalytic performance of TiO 2 photocatalytic paper was shown by decomposing methyl orange under UV light irradiation.…”
Section: Tio 2 Photocatalytic Papermentioning
confidence: 99%